2011
DOI: 10.1042/bj20100507
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of the neutral amino acid transporter SNAT2 regulates transport activity through voltage-dependent processes

Abstract: Sodium-coupled neutral amino acid transporter 2 (SNAT21) belongs to the SLC38 family of solute transporters. Transport of 1 amino acid molecule into the cell is driven by the co-transport of 1 Na+ ion. The functional significance of the C-terminus of SNAT2, which is predicted to be located in the extracellular space, is currently unknown. Here, we removed 13 amino acid residues from the SNAT2 C-terminus and studied the effect of the deletion on transporter function. The truncation abolished amino acid transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The extracellular orientation of C termini of SNAT family proteins have previously been determined both experimentally (35) and by computer simulation (9,17,36), which is consistent with our results. However, based primarily on theoretical prediction, but not on experimental data, previous published studies, including those from our laboratory, suggest an intracellular orientation of N termini for SNAT family proteins (10,11,17,36,37).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The extracellular orientation of C termini of SNAT family proteins have previously been determined both experimentally (35) and by computer simulation (9,17,36), which is consistent with our results. However, based primarily on theoretical prediction, but not on experimental data, previous published studies, including those from our laboratory, suggest an intracellular orientation of N termini for SNAT family proteins (10,11,17,36,37).…”
Section: Discussionsupporting
confidence: 82%
“…However, based primarily on theoretical prediction, but not on experimental data, previous published studies, including those from our laboratory, suggest an intracellular orientation of N termini for SNAT family proteins (10,11,17,36,37). Based on the prediction by HHpred, we noticed that SNAT family proteins share a certain degree of sequential homologies with plant auxin permease, auxin1, and bacterial transporters, AdiC and Mhp1.…”
Section: Discussionmentioning
confidence: 95%
“…SNAT2 is a mammalian transceptor that transports neutral amino acid and senses amino acid availability [ 36 ]. The long soluble N-terminus of SNAT2 senses intracellular amino acid content thereby stabilizes the amino acid pool, while the short extracellular C-terminus regulates transport activity [ 42 ]. In contrast to the yeast and mammalian transceptors, which have low specificity and respond to amino acid availability, the Leishmania arginine sensor responds only to arginine availability.…”
Section: Discussionmentioning
confidence: 99%
“…2004), is strongly inhibited by acidosis (Baird et al 2006;Evans et al 2007;Evans et al 2008) and inhibited in CKD (Asola et al 2001). No change was seen in SNAT2 expression (Table 6), but studies in vitro have shown that acidosis directly inhibits this transporter protein (Baird et al 2006;Zhang et al 2011) independent of gene expression (Evans et al 2007;Evans et al 2008). However this inhibition by acid has previously only been studied acutely, and the corresponding chronic effects of acid on this transporter in the context of exercise and mechanical stress merit further investigation.…”
Section: Amino Acid Depletionmentioning
confidence: 95%